1999
DOI: 10.1161/01.cir.99.9.1209
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Features of Ductus Arteriosus Constriction and Restrictive Foramen Ovale in d-Transposition of the Great Arteries

Abstract: Background-Although most neonates with d-transposition of the great arteries (TGA) have an uncomplicated preoperative course, some with a restrictive foramen ovale (FO), ductus arteriosus (DA) constriction, or pulmonary hypertension may be severely hypoxemic and even die shortly after birth. Our goal was to determine whether prenatal echocardiography can identify these high-risk fetuses with TGA. Methods and Results-We reviewed the prenatal and postnatal echocardiograms and outcomes of 16 fetuses with TGA/inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
130
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 32 publications
10
130
0
1
Order By: Relevance
“…Indeed, there is now a significant number of reported cases of patients with TGA who presented either at autopsy without prior diagnosis or of children who were moribund on admission and who died within a few hours of birth. [5][6][7][8][9]15,16 We showed that prenatal diagnosis reduced the mortality rate of patients with TGA. 3 However, Soongswang et al 5 and Maeno et al 9 reported 3 cases of prenatally diagnosed TGA in patients who died immediately after birth.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Indeed, there is now a significant number of reported cases of patients with TGA who presented either at autopsy without prior diagnosis or of children who were moribund on admission and who died within a few hours of birth. [5][6][7][8][9]15,16 We showed that prenatal diagnosis reduced the mortality rate of patients with TGA. 3 However, Soongswang et al 5 and Maeno et al 9 reported 3 cases of prenatally diagnosed TGA in patients who died immediately after birth.…”
Section: Discussionmentioning
confidence: 96%
“…Prenatal features of the foramen ovale and of the ductus arteriosus were reviewed retrospectively for the period November 1997 and November 1999 and described prospectively during the second period of the study. According to Maeno et al 9 and Wilson et al, 14 the foramen ovale was considered at risk of postnatal early restriction if the aneurysmal septum primum bulged Ͼ50% of the way across to the left atrial free wall; if the angle between the septum primum and the rest of the atrial septum was Ͻ30°; or if the septum did not have the typical swinging motion during the cardiac cycle. For the ductus arteriosus, the diameter was measured at the narrowest portion, typically at the pulmonary end.…”
Section: Echocardiographic Examinations and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 Premature closure of the foramen ovale and/or ductus arteriosus also has been shown to be associated with severe postnatal hypoxemia [16][17][18] and pulmonary hypertension, thought to occur as a result of pulmonary vascular remodeling. 18 The rationale to discontinue the PGE 1 infusion is based on a theoretical risk that if the left ventricle (LV) is exposed to a lower PVR preoperatively, it is less likely to adapt to the sudden increase in LV afterload that occurs following the arterial switch procedure. We did not identify an obvious increased risk of cardiorespiratory stability as judged by the duration of assisted ventilation, need for cardiotropic support or frequency of cardiac dysrhythmias.…”
Section: Resultsmentioning
confidence: 99%
“…Antenatal ductal constriction is known to be associated with persistent pulmonary hypertension in neonates. (12,24) In infants with transposition of the great arteries and intact ventricular septum as young as one week considerable intimal proliferation with luminal occlusion has been reported. (12,25) With persistence of extensive bronchial-pulmonary shunts resulting in increased blood flow, and inherent structural defects of the muscular pulmonary arteries secondary to chromosomal abnormalities, arteriolar spasm and a gradual increase in pulmonary vascular resistance follows.…”
Section: Discussionmentioning
confidence: 99%